Bond behavior in NSM-strengthened masonry. (1st July 2018) - Maljaee, Hamid; Ghiassi, Bahman; Lourenço, Paulo B.
Highlights: The bond behavior in NSM system was investigated by testing 36 FRP-strengthened bricks. A new test setup was developed to avoid the pre-compression load before test. Majority of specimens failed at the adhesive-to-brick interface. Accuracy of existing bond prediction models was evaluated using a large database. A fracture-based model was proposed in this study to predictthe bond strength. Abstract: Near Surface Mounted (NSM) reinforcement is an interesting technique for seismic strengthening of masonry and historical structures. Despite having several advantages compared to conventional techniques, little attention has been given to understanding the involved mechanisms (such as bond behavior) in the performance of masonry components strengthened with this reinforcement technique. This study presents an experimental and analytical investigation on the bond performance of NSM-strengthened masonry bricks aiming at filling the existing gaps in the available experimental results in the literature. The main focus is on the effect of test setup and bond length, but attention has also been given to the groove size and loading regime effect on the bond performance. The accuracy of the existing bond strength prediction models is also assessed and the required modifications are proposed.